1996
DOI: 10.1056/nejm199602153340703
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma HIV-1 RNA and CD4+ Lymphocyte Counts and the Risk of Progression to AIDS

Abstract: Treatment-induced changes in the plasma HIV-1 RNA level and the CD4+ lymphocyte count, taken together, are valid predictors of the clinical progression of HIV-related disease and can be used to assess the efficacy of zidovudine and possibly other antiretroviral drugs as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
275
2
6

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 671 publications
(289 citation statements)
references
References 29 publications
6
275
2
6
Order By: Relevance
“…Their evaluation suggested that only if the unadjusted treatment effect was more than four times its standard error would it be possible to validate that a surrogate was explaining some of the treatment effect. O'Brien et al [7] used P (FGS) to evaluate the proportion of zidovidine's (AZT) effect on progression to AIDS explained by HIV viral RNA copy number and by CD4. The authors used estimates of P (FGS) to conclude that viral RNA explained a larger proportion of AZT's effect than CD4, but using them both as joint surrogates in a Cox model explained the largest proportion.…”
Section: Introductionmentioning
confidence: 99%
“…Their evaluation suggested that only if the unadjusted treatment effect was more than four times its standard error would it be possible to validate that a surrogate was explaining some of the treatment effect. O'Brien et al [7] used P (FGS) to evaluate the proportion of zidovidine's (AZT) effect on progression to AIDS explained by HIV viral RNA copy number and by CD4. The authors used estimates of P (FGS) to conclude that viral RNA explained a larger proportion of AZT's effect than CD4, but using them both as joint surrogates in a Cox model explained the largest proportion.…”
Section: Introductionmentioning
confidence: 99%
“…Prediction of the treatment effect at the trial level is undoubtedly central to the problem of surrogate validation, and some approaches are in fact based exclusively on trial-level information [7]. Prediction of the true endpoint at the individual level is only incidental to the validation problem, even though the correlation between the surrogate and the true endpoints is one of the elements to consider in the evaluation process [27,28]. Although a good correlate may not be a good surrogate [9], a poor correlate is even less likely to be one.…”
Section: Discussionmentioning
confidence: 99%
“…Since differences of less than 0.5 log are not considered clinically significant (Saag et al 1996), these results were satisfactory, confirming that the NASBA system is a reliable method for assessing viral load. However, it is noteworthy that the determination of this 0.5 log range has been based mostly on studies using bDNA and PCR assays , O´Brien et al 1996.…”
Section: Discussionmentioning
confidence: 99%